Non-Siloxane Sensory Modifiers

Crosslinked elastomers formed by polyolefins and polyether crosslinking agents with C-Si-C bonds address the need for sensory modifiers in skin care that mimic silicone elastomers' skin feel without using silicones, achieving compatibility with organic solvents.

JP2025511328APending Publication Date: 2025-04-15DOW SILICONES CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024558370
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-07
Filing Date
2023-02-16
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing sensory modifiers in skin care formulations, such as silicone elastomers, rely on siloxane bonds, which can include volatile components and limit the development of alternatives that provide a similar skin feel without using silicones.

Method used

The development of crosslinked elastomers composed of polyolefins crosslinked with polyether crosslinking agents, forming carbon-silicon-carbon (C-Si-C) bonds, which do not include siloxane (Si-O-Si) bonds, to create a skin feel similar to silicone elastomers while being compatible with various organic solvents.

Benefits of technology

The resulting elastomers provide a skin feel similar to silicone elastomers and are compatible with a range of organic solvents, allowing for their use in various cosmetic formulations without the need for silicones.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511328000001
    Figure 2025511328000001
  • Figure 2025511328000002
    Figure 2025511328000002
  • Figure 2025511328000003
    Figure 2025511328000003
Patent Text Reader

Abstract

The composition contains a crosslinked elastomer comprising a polyolefin backbone crosslinked via a polyether chain, the crosslinked elastomer having a carbon-silicon-carbon bond between the polyolefin backbone and the polyether chain, and the crosslinked elastomer being free of Si-O-Si bonds.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention is a crosslinked elastomer that is free of siloxane bonds, compositions that include the crosslinked elastomer, and processes for producing the crosslinked elastomer. [Background technology]

[0002] Introduction U.S. Patent No. 9,999,586 ('586) teaches that silicone elastomers are believed to be one of the best sensory modifiers used in skin care formulations. '586 identifies the unique structure of silicone elastomers as the reason they have a different skin feel than any silicone fluid or cationic quaternary compounds previously used as sensory modifiers. The feel of silicone elastomers has been described as "velvety, powdery, smooth, and cushion-like." Silicone elastomers are used as sensory modifiers in solvent swollen pastes where the elastomers are solvent swollen and blended to break the elastomer into pieces to form a paste. Desirably, the solvent swollen elastomer pieces have an average particle size ranging from 1 to 1,000 micrometers, preferably 1 to 100 micrometers, more preferably 1 to 50 micrometers, and even more preferably 1 to 25 micrometers. Smaller particles are more desirable for a smoother feel.

[0003] However, because silicones can undesirably contain low molecular weight volatile silicones and cyclics, it is desirable to identify sensory modifiers that provide a similar feel to silicone elastomers, but that have materials other than silicone.

[0004] US Patent No. 9999586 describes silicone modified polyolefins as a possible substitute for silicone elastomers for use as a sensory modifier for use in skin care formulations.Silicone modified polyolefins have similar sensory feel to silicone elastomers, but seek to contain polyolefins and silicone polymer components to reduce the amount of silicone polymer in materials.Silicone modified polyolefins still rely on silicone polymers to achieve the unique structure associated with the desired skin feel of sensory modifiers.

[0005] It is further desirable that the elastomers and elastomer pastes are compatible with various organic solvents used in cosmetic formulations so that the elastomers can be incorporated into various cosmetic formulations. Typical organic solvents include octyl methoxycinnamate, ethylhexyl salicylate, sunflower oil, squalane, and mineral oil. Compatible elastomers and pastes form clear or hazy mixtures with the solvent, but do not become cloudy, opaque, or phase separate from the solvent.

[0006] It is desirable to identify elastomers that can be sensory modifiers with similar skin feel as the silicone elastomers commonly used in the cosmetics industry for sensory modifiers, but without the need for silicones. It is further desirable for the elastomer to be solvent compatible with the various organic solvents used in cosmetic formulations. Summary of the Invention

[0007] The present invention provides elastomers that can be sensory modifiers with similar skin feel to silicone elastomers, but without the need for silicones.The present invention also provides elastomers that can form pastes that are compatible with a variety of organic solvents, at least as compatible as similar siloxane elastomer pastes common in the cosmetic field.

[0008] The present invention is the result of the discovery that crosslinking a polyolefin with a polyether crosslinker and linking the polyolefin and polyether with carbon-silicon-carbon (C-Si-C) bonds produces an elastomer that can be solvent swollen and mixed into a paste with a skin feel similar to pastes made with silicone elastomers. It is believed that the combination of C-Si-C bonds and polyether crosslinks causes a particular skin feel. It is believed that the unique bond angles produced by the C-Si-C bonds contribute to a desirable morphology that promotes the desired skin feel. The polyether provides the elastomer with desirable compatibility, allowing it to be formulated into a variety of formulations, and provides desirable mobility between the polyolefin backbones. It is believed that the C-Si-C bonds and polyether crosslinks together result in an elastomer with a skin feel in a solvent swollen paste similar to pastes made from silicone elastomers.

[0009] In a first aspect, the invention is a composition comprising a crosslinked elastomer comprising a polyolefin backbone crosslinked via a polyether chain, the crosslinked elastomer having carbon-silicon-carbon bonds between the polyolefin backbone and the polyether chain, the crosslinked elastomer not containing Si-O-Si bonds as required in silicones.

[0010] In a second aspect, the invention is a process for making the composition of the first aspect, comprising: (a) a hydrosilane-functional polyolefin having no Si-O-Si bonds; (b) a polyether crosslinker having at least two terminal alkenyl groups and having no Si-O-Si bonds; (c) a hydrosilylation catalyst; and (d) an organic solvent, to provide a crosslinked elastomer by conducting a hydrosilylation reaction using a reaction composition comprising: (a) a hydrosilane-functional polyolefin having no Si-O-Si bonds; (b) a polyether crosslinker having at least two terminal alkenyl groups and having no Si-O-Si bonds; (c) a hydrosilylation catalyst; and (d) an organic solvent.

[0011] The compositions of the present invention are useful in sensory modifiers for skin care products. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Test methods refer to the test method most recent as of the priority date of this document unless a date is given with the test method number. Reference to a test method includes both a reference to the testing society and the test method number. The following test method abbreviations and identifiers apply herein: ASTM refers to American Society for Testing and Materials test methods, EN refers to European Norm, DIN refers to Deutsches Institut fur Normung, ISO refers to International Organization for Standards, and UL refers to Underwriters Laboratory.

[0013] Products identified by trade names refer to compositions available under those trade names as of the priority date of this document.

[0014] "Plurality" means two or more. "And / or" means "and, or alternatively." All ranges are inclusive of the endpoints unless otherwise indicated.

[0015] The term "interpolymer" refers to polymers prepared by the polymerization of at least two different types of monomers. The term interpolymer includes the term copolymer, which refers to polymers prepared from two different types of monomers, and polymers prepared from more than two different types of monomers.

[0016] For the polymers herein, the number average molecular weight ("Mn (GPC) ").

[0017] Gel permeation chromatography method for molecular weight The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160 degrees Celsius and the column compartment was set at 150 degrees Celsius. The columns were one Agilent PLgel MIXED 7.5×50 mm, 20 μm linear mixed bed guard column and four Agilent PLgel MIXED-A 7.5×300 mm, 20 μm linear mixed bed columns. The chromatography solvent was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The injection volume used was 200 microliters and the flow rate was 1.0 milliliters / min.

[0018] Calibration of the GPC column set was performed using Agilent EasiCal polystyrene standards (EasiCal PS-1 and EasiCal PS-2). Each EasiCal system consisted of two different spatulas supporting a mixture of five polymer standards (approximately 5 mg) to obtain 20 molecular weight points ranging from approximately 580 to 6,570,000 g / mol. Individual spatulas were added to septum-capped vials, sealed, and loaded into the PolymerChar autosampler. Utilizing the PolymerChar Instrument Control Software, 8 mL of solvent was added to each vial and the standards were dissolved at 160 °C under high speed shaking for 15 min prior to injection into the chromatographic system. A third order polynomial was used to fit the nominal polystyrene standard peak molecular weights to obtain molecular weight equivalent calibration points at each chromatographic intercept.

[0019] The total plate count of the GPC column set was performed using decane (3% v / v in TCB introduced via a micropump). The plate count of the chromatography system should exceed 18,000 for four Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns.

[0020] Samples were prepared semi-automatically using the PolymerChar Instrument Control Software with a sample target weight of 2 mg / mL, and solvent was added to septum-capped vials via a PolymerChar high-temperature autosampler. Samples were dissolved at 160°C for 2 hours under rapid shaking.

[0021] Mn (GPC) , Mw (GPC) , and Mz (GPC) The calculation of was based on GPC results using the internal IR5 detector (measurement channel) of a PolymerChar GPC-IR chromatograph according to Equations 1-3. Using PolymerChar GPCOne™ software, the baseline-subtracted IR chromatogram at each equally spaced data collection point (i) was converted to a polyethylene equivalent molecular weight obtained from a narrow standard calibration curve of the equivalent chromatographic data points (i). Equations 1-3 are as follows:

[0022]

number

[0023] To monitor deviations over time, a flow rate marker (3% v / v decane in solvent) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (apparent)) of each sample by matching the RV of the respective decane peak in the sample (RV(FM sample)) with the RV of the decane peak in the narrow standard calibration (RV(FM calibrated)). Any change in time of the decane marker peak was then assumed to be related to a linear shift in the flow rate (flow rate (effective)) throughout the run. After calibrating the system based on the flow rate marker peak, the effective flow rate (relative to the narrow standard calibration) is calculated as per Equation 4. Processing of the flow rate marker peak was performed via PolymerChar's GPCOne™ software. For acceptable flow rate correction, the effective flow rate should be within ±0.7% of the apparent flow rate.

[0024] Flow (effective) = Flow (apparent) × (RV(FM calibrated) / RV(FM sample)) (Equation 4)

[0025] The compositions of the present invention comprise crosslinked elastomers comprising a polyolefin backbone crosslinked through polyether chains and further characterized by having carbon-silicon-carbon (C-Si-C) bonds connecting the polyolefin backbone to the polyether chains and no siloxane (Si-O-Si) bonds.

[0026] The polyolefin backbone is a homopolymer or interpolymer comprising interpolymerized monomers polymerized through carbon-carbon double bonds (C=C). Desirably, the polyolefin backbone comprises polymerized alkenes selected from the group consisting of alkenes having 2 or more, preferably 3 or more, 4 or more, 5 or more, 6 or more, 7 or more, or even 8 or more carbon atoms, but typically 10 or less, 9 or less, 8 or less, 7 or less, or 6 or less carbon atoms. Most desirably, the polyolefin backbone comprises an interpolymer comprising polymerized ethylene and octene.

[0027] The polyolefin backbone further comprises a copolymerized monomer that produces a pendant carbon chain that includes a carbon-silicon (C-Si) bond that connects a silicon atom to the polyolefin backbone, and preferably the pendant carbon chain terminates with a C-Si. Crosslinking occurs through the Si of the C-Si bond, specifically through a C-Si-C bond that includes a C-Si bond. The polyolefin can include a copolymerized alkenyl silane, such as, for example, 7-octenyldimethylsilane and / or 5-hexenyldimethylsilane. Crosslinking can then occur through the silicone hydride bond (Si-H) bond of the silane to produce a C-Si-C bond between the backbone and the polyether crosslinker.

[0028] Desirably, the polyolefin backbone is an interpolymer comprising or consisting of polymerized monomer segments of the following: (a) 20 to 35 mole percent octene, (b) 65 to 80 mole percent ethylene, and (c) 1 to 10 mole percent of any combination of one or more of 7-octenyldimethylsilane and 5-hexenyldimethylsilane.

[0029] The polyether chains bridging the polyolefin backbone typically comprise polyether units selected from -RO- groups, where R is an alkylene having 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, or even 7 or more carbon atoms, while typically having 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or even 3 or less carbon atoms. For example, the polyether chains can comprise any combination of any one or more of polyethylene oxide, polypropylene oxide, and polybutylene oxide.

[0030] The polyether chains crosslinking the polyolefin backbone typically contain 3 or more, 5 or more, 10 or more, 15 or more, or even 20 or more -RO- groups, while generally containing up to 100, up to 75, up to 60, up to 50, up to 45, up to 40, up to 30, up to 25, or even up to 20 -RO- groups.

[0031] The crosslinked elastomer desirably comprises or consists of the following copolymerized polymer segments (a) to (c): (a) 20 to 35 mole percent (mol %) of a combination of one or more segments having an average chemical structure -CHCHR'-; (b) 65 to 80 mol % of -CH2CH2-, and (c) 1 to 10 mole percent of -CH2CHA-; The mole % is based on the moles of copolymerized polymer segments in the crosslinked elastomer, and each R' at each occurrence is independently selected from the group consisting of alkyl groups having 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, or even 6 or more carbon atoms, but at the same time typically having 8 or less, 7 or less, or even 6 or less carbon atoms, and A has the following average chemical structure (I): -(CH2) n Si(CH3)2-BD (I) [(In the formula, n is, independently at each occurrence, a value ranging from 4 to 6, and may be 4, 5, or 6; B is -(CH2)3O(RO) p’ (CH2)3- (In the formula, each R is independently as defined above at each occurrence, and is preferably a combination of one or both of alkylene groups selected from -CHCH- and -CHCH(CH)- groups; the subscript p' has a value of 15 or greater, or 20 or greater and at the same time 25 or less; D is a -Si(CH3)2(CH2) of another A group such that component B is a bridging group connecting two backbone groups of other copolymerized polymer segments. n - group silicon.

[0032] The composition of the present invention may further comprise a solvent together with the crosslinked elastomer. The crosslinked elastomer may be swollen with an elastomer to form a solvent-swollen elastomer. A solvent-swollen elastomer is an elastomer that has absorbed a solvent. Generally, a solvent-swollen elastomer has a larger volume than the elastomer alone without the presence of the solvent.

[0033] Typical solvents include hydrocarbons, esters, and ethers. Examples of suitable solvents include any one or more combinations selected from isohexadecane, isododecane, undecane, tridecane, dicaprylyl carbonate, isodecyl neopentanoate, and di-n-octyl ether.

[0034] Desirably, the composition comprises a solvent at a concentration of 90% by weight or more, or even 95% by weight or more, but at the same time typically not more than 97% by weight based on the weight of the composition.

[0035] The composition can include particulates of a solvent swollen elastomer. Desirably, the composition has a particle size of 1 micrometer or more, 5 micrometers or more, 10 micrometers or more, 20 micrometers or more, 30 micrometers or more, 40 micrometers or more, 50 micrometers or more, 75 micrometers or more, 100 micrometers or more, 125 micrometers or more, 150 micrometers or more, 175 micrometers or more, 200 micrometers or more, 225 micrometers or more, 250 micrometers or more, 275 micrometers or more, 300 micrometers or more, 325 micrometers or more, 350 micrometers or more, 375 micrometers or more, 400 micrometers or more, 425 micrometers or more, or even 450 micrometers or more. Sometimes the solvent swollen elastomers have an average particle size of 500 micrometers or less, 475 micrometers or less, 450 micrometers or less, 425 micrometers or less, 400 micrometers or less, 375 micrometers or less, 350 micrometers or less, 325 micrometers or less, 300 micrometers or less, 275 micrometers or less, 250 micrometers or less, 225 micrometers or less, 200 micrometers or less, 175 micrometers or less, 150 micrometers or less, 125 micrometers or less, 100 micrometers or less, 75 micrometers or less, 50 micrometers or less, 25 micrometers or less, 20 micrometers or less, or even 10 micrometers or less.

[0036] The following elastomer particulate sizing method is used to determine the average particle size of the solvent swollen elastomer particulates. The elastomer particulate sizing method is a laser diffraction method using a Mastersize 3000 (Malvern Panalytical). A sample of elastomer paste is prepared by placing 1.00 grams (g) of solvent swollen elastomer in a 20 g dental mixing cup and mixing with a speed mixer at 3500 revolutions per minute (RPM) for 30 seconds. 0.5 g of isododecane is added and mixed at 3500 RPM for 30 seconds. Another 0.5 g of isododecane is added and mixed at 3500 RPM for 30 seconds. Another 1.0 g of isododecane is added and mixed at 3500 RPM for 30 seconds. Another 2.0 g of isododecane is added and mixed at 3500 RPM for 30 seconds. Add another 2.0 g of isododecane and mix at 3500 RPM for 30 seconds. Add another 4.0 g of isododecane and mix at 3500 RPM for 10 seconds to obtain an elastomer paste, which is a solvent swollen elastomer containing fine particles of solvent swollen elastomer. Add a sample of the elastomer paste to a hydro SV fluid cell for average particle size determination using a Masterizer 3000. Collect and analyze data using Mastersizer v.3.81 software, assuming non-spherical particles, material refractive index of 1.5 (standard olefin), dispersant refractive index of 1.42 (isododecane), and test for obscuration from 2 to 25%.

[0037] The composition may include sunscreens, colorants, and / or sun care additives such as titanium dioxide, zinc oxide, or combinations thereof, at concentrations up to 20% by weight of the composition.

[0038] The invention also includes a process for preparing the compositions of the invention by providing a crosslinked elastomer by conducting a hydrosilylation reaction with a reaction composition comprising: (a) a hydrosilane-functional polyolefin having no Si-O-Si bonds; (b) a polyether crosslinker having at least two terminal alkenyl groups and no Si-O-Si bonds; (c) a hydrosilylation catalyst; and (d) an organic solvent.

[0039] Hydrosilane-functional polyolefins that do not contain Si-O-Si bonds can be prepared according to the teachings of U.S. Patent No. 6,624,254. The hydrosilane-functional polyolefins form a crosslinked elastomeric polyolefin backbone and therefore can be characterized as described herein above for the polyolefin backbone. Desirably, the hydrosilane-functional polyolefins have a number average molecular weight (Mn) of 15,000 or more, 20,000 or more, 25,000 or more, 30,000 or more, 35,000 or more, 40,000 or more, 45,000 or more, or even 50,000 or more. (GPC) ), but at the same time desirably have an Mn of 150,000 or less, 146,000 or less, 140,000 or less, 120,000 or less, 100,000 or less, 80,000 or less, 70,000 or less, 60,000 or less, 55,000 or less, 50,000 or less, 45,000 or less, or even 40,000 or less. (GPC) has.

[0040] The hydrosilane-functional polyolefin is a random interpolymer (as opposed to a block interpolymer). Desirably, the hydrosilane-functional polyolefin is a random interpolymer comprising or consisting essentially of the following copolymerized segments (apart from possible end groups on the interpolymer): -(CHCHR')-, -R''-, and -(CHCHG)-, wherein: Each R' may be the same or different from the other R' groups, and each R' is independently selected at each occurrence from alkyl groups having 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, or even 7 or more carbon atoms, but at the same time typically having 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 carbon atoms or less; Each R" may be the same or different from the other R" groups, and each R" is independently selected at each occurrence from alkylene having 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, or even 7 or more carbon atoms, but at the same time typically having 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 carbon atoms; Each G may be the same or different from the other G groups, and each G may independently at each occurrence have the following average chemical structure: -R 3 SiR 4 2H (in the formula, Each R 3 is another R 3 may be the same or different for each R 3 are independently selected from the group consisting of alkylene groups having 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, or even 7 or more, but at the same time typically 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 carbon atoms; Each R 4 is another R 4 may be the same or different for each R 4 is independently at each occurrence selected from the group consisting of hydrogen and alkyl groups having 1 or more, 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, or even 7 or more, but at the same time typically 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, 3 or less, or even 2 carbon atoms.

[0041] The -(CHCHR')- segments are typically present in the hydrosilane-functional polyolefin at a concentration of 20 mole percent (mol %) or more, 25 mole % or more, or even 30 mole % or more, while at the same time, typically at a concentration of 35 mole % or less, 30 mole % or less, or even 25 mole % or less, where the mole % is based on the total moles of copolymerized segments.

[0042] The -R''- segments are typically present in the hydrosilane functional polyolefin at a concentration of 65 mol % or more, 70 mol % or more, or even 75 mol % or more, while at the same time, typically at a concentration of 80 mol % or less, 75 mol % or less, or even 70 mol % or less, the mol % being based on the total moles of copolymerized segments.

[0043] The -(CHCHG)- segments are typically present in the hydrosilane-functional polyolefin at a concentration of 1 mol % or more, 5 mol % or more, or even 7.5 mol % or more, while at the same time, typically at a concentration of 10 mol % or less, 7.5 mol % or less, or even 5 mol % or less, the mol % being relative to the total moles of copolymerized segments.

[0044] The hydrosilane functional polyolefin may be an interpolymer of (a) 20-35 mole % 1-octene, (b) 65-80 mole % ethylene, and (c) 1-10 mole % of any combination of one or both of 7-octenyldimethylsilane and 5-hexenyldimethylsilane, where the mole percentages are based on the total moles of 1-octene, ethylene, 7-octenyldimethylsilane, and 5-hexenyldimethylsilane, and the mole percentages are based on the total moles of (a), (b), and (c).

[0045] The polyether crosslinker contains or comprises polyether units selected from -RO- groups, where R is an alkylene having 2 or more, 3 or more, 4 or more, 5 or more, 6 or more, or even 7 or more carbon atoms, while typically having 8 or less, 7 or less, 6 or less, 5 or less, 4 or less, or even 3 or less carbon atoms. Generally, the polyether crosslinker contains 3 or more, 5 or more, 10 or more, 15 or more, or even 20 or more -RO- groups, while generally containing 100 or less, 75 or less, 60 or less, 50 or less, 45 or less, 40 or less, 30 or less, 25 or less, or even 20 or less -RO- groups.

[0046] The hydrosilylation catalyst can be any catalyst useful for catalyzing hydrosilylation reactions. Typically, the hydrosilylation catalyst is a platinum-based catalyst. Platinum-based hydrosilylation catalysts include compounds and complexes such as platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane (Karstedt's catalyst), HPtCl, di-μ.-carbonyldi-.π.-cyclopentadienyldinickel, platinum-carbonyl complexes, platinum-divinyltetramethyldisiloxane complexes, platinum cyclovinylmethylsiloxane complexes, platinum acetylacetonate (acac), platinum black, platinum compounds such as chloroplatinic acid, chloroplatinic acid hexahydrate, reaction products of chloroplatinic acid with monohydric alcohols, platinum bis(ethylacetoacetate), platinum bis(acetylacetonate), platinum dichloride, and complexes of platinum compounds with olefins or low molecular weight organopolysiloxanes, or platinum compounds microencapsulated in a matrix or core-shell structure. The hydrosilylation catalyst may be part of a solution containing complexes of platinum with low molecular weight organopolysiloxanes, including 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane complexes with platinum. These complexes may be microencapsulated in a resin matrix. The catalyst may be 1,3-diethenyl-1,1,3,3-tetramethyldisiloxane complexes with platinum.

[0047] Typical solvents include hydrocarbons, esters, and ethers. Examples of suitable solvents include any one or more combinations selected from isohexadecane, isododecane, undecane, tridecane, dicaprylyl carbonate, isodecyl neopentanoate, and di-n-octyl ether. EXAMPLES

[0048] Synthesis of Hydrosilane Functional Polyolefin (HFP) Ethylene / octene / silane copolymerizations were carried out in a 2 L autoclave batch reactor designed for the homo- and copolymerization of ethylene. The reactor was equipped with an electric heating zone and an internal cooling coil containing cooling glycol. Both the reactor and the heating / cooling system were controlled and monitored by a process computer. A dump valve was fitted to the bottom of the reactor, which allowed the reactor contents to be emptied into a dump pot and released to the atmosphere.

[0049] All chemicals used in the polymerization, as well as the catalyst solution, were passed through a purification column before use. ISOPAR-E, 1-octene, ethylene, and silane monomers were also passed through the column. Ultra-high purity grade nitrogen (Airgas) and hydrogen (Airgas) were used. The catalyst cocktail was prepared in an inert glove box by mixing the scavenger (MMAO-3A), activator (bis(hydrogenated tallow alkyl)methyl tetrakis(pentafluorophenyl)borate amine), and precatalyst (zirconium, dimethyl[[2,2′′-[1,3-propanediylbis(oxy-κO)]bis[3′,5,5′-tris(1,1-dimethylethyl)-5′-methyl[1,1′:3′,1′-terphenyl]-2′-olato-κO]](2-)]-(ACI)) with the appropriate amount of toluene to achieve the desired molar concentration solution. The solution was then diluted with ISOPAR-E or toluene to obtain the desired amount for polymerization and drawn into a syringe for transfer to a catalyst shot tank.

[0050] In a typical polymerization, the reactor was loaded with ISOPAR-E and 1-octene via separate flow meters. The silane monomer was then added via a shot tank piped in through an adjacent glove box. After the solvent / comonomer addition, hydrogen (if required) was added while the reactor was heated to the polymerization set point of 120° C. Ethylene was then added to the reactor via a flow meter at the desired reaction temperature to maintain the predetermined reaction pressure set point. The catalyst solution was transferred via syringe to the shot tank and then added to the reactor via a high pressure nitrogen stream after the reactor pressure set point was reached. A run timer was started upon catalyst injection, after which an exotherm as well as a drop in reactor pressure were observed, indicating a successful run.

[0051] Ethylene was then added using a pressure controller to maintain the reaction pressure set point in the reactor. The polymerization was carried out to the set ethylene uptake, after which the agitator was stopped and the bottom dump valve was opened to empty the reactor contents into a dump pot. The pot contents were poured into a tray, which was placed in a fume hood to allow the solvent to evaporate overnight. The tray with the remaining polymer was then transferred to a vacuum oven and heated to 100° C. under reduced pressure to remove any remaining solvent. After cooling to ambient temperature, the polymer was weighed for yield / efficiency and transferred to a container for storage and analytical testing. The polymerization conditions are shown in Table 1. The polymer properties are shown in Table 2.

[0052] [Table 1]

[0053] [Table 2] *1 Mole % based on total moles of monomer in polymer as determined by 1 H NMR. A ODMS = 7-octenyldimethylsilane. B HDMS = 5-hexenyldimethylsilane.

[0054] Number average molecular weight (Mn), weight average molecular weight (Mw), and polydispersity (Mw / Mn) are determined by gel permeation chromatography (GPC) according to the Gel Permeation Chromatography method for molecular weight presented herein above.

[0055] Monomer ratio information was obtained by proton nuclear magnetic resonance spectroscopy ( 1 The NMR spectra were determined by H NMR. Samples were dissolved in tetrachloroethane-d2 (with or without 0.001M Cr(acac)3) in 8 mm NMR tubes. The concentration was approximately 100 mg / 1.8 mL. The tubes were then heated in a heating block set at 110 °C. The sample tubes were repeatedly vortexed and heated to obtain a homogeneous flowing fluid. 1 H NMR spectra were acquired using standard single pulse 1 H NMR experiments were performed using the following acquisition parameters: 70 s repeat delay, 17.2 μs 90 degree pulse, 32 scans. The spectrum was centered at 1.3 ppm with a spectral width of 20 ppm. All measurements were performed at 110 °C without sample rotation. 1 H NMR spectra were referenced to the resonance peak of the solvent (residual protonated tetrachloroethane) at 5.99 ppm. For samples containing Cr, data were acquired with a 16 second repeat wait time and 128 scans.

[0056] Glass transition temperatures (Tg) and melting temperatures (Tm) were determined using differential scanning calorimetry (DSC) according to the following method. Each sample (0.5 g) was compression molded into a film at 5000 psi and 190°C for 2 minutes. Approximately 5-8 mg of film sample was weighed and placed into a DSC pan. A lid was crimped onto the pan to ensure a closed atmosphere. Unless otherwise stated, the sample pan was placed into the DSC cell and then heated at a rate of approximately 10°C / min to a temperature of 180°C for PE (230°C for PP). The sample was held at this temperature for 3 minutes. The sample was then cooled at a rate of 10°C / min to -90°C for PE (-60°C for PP) and held isothermally at that temperature for 3 minutes. The sample was then heated at a rate of 10°C / min until completely melted (second heat). The melting point (Tm) of each polymer was determined, unless otherwise stated. m ) and glass transition temperature (T g ) is determined from the second heating curve and is the crystallization temperature (T c ) was determined from the first cooling curve. T m and T c The peak temperatures of each of the three samples were recorded. The percent crystallinity was calculated based on the heat of fusion (H ) determined from the second heating curve. f ) by the theoretical heat of fusion of 292 J / g for PE (165 J / g for PP) and multiplying this amount by 100 (e.g., crystallinity % = (Hf / 292 J / g) x 100 for PE). m A peak is typically observed, where the T of the polymer m The highest temperature peak is recorded as the

[0057] Table 3 provides information regarding materials for making HFP1 and HFP2.

[0058] [Table 3]

[0059] Preparation of crosslinked elastomers and elastomer gel pastes Table 4 lists the ingredients for use in preparing the crosslinked elastomers.

[0060] [Table 4] SYL-OFF is a trademark of Dow Silicones Corporation

[0061] Example 1. First, prepare a 10.0 wt% solution of HFP1 in isododecane by adding 10 g of HFP1 and 90 g of isododecane to a first glass jar, seal the jar and roll on a three-mill roll for 48 hours to form a homogenous solution. Then, add 29.71 g of the homogenous solution from the first glass jar to a second glass jar along with 0.56 g of diallyl propylene glycol crosslinker and 29.71 g of isododecane. Add a stirring cloth. Place the jar in an 80°C hot water bath and begin stirring. Once the contents reach a temperature of 75-80°C, inject 0.12 g of catalyst into the jar and continue mixing until gelation occurs. Place the jar at 70°C for 4 hours to obtain crosslinked elastomer Example 1.

[0062] Prepare an elastomer gel paste from Example 1 by placing 59.08 g of Example 1 in a Waring Blender and shearing for 20 seconds each at settings 1, 3, and 5 without scraping or stopping between settings. Add 5.91 g of isododecane and shear for 30 seconds each at settings 1, 2, and 3. Use intermediate settings to ensure good mixing. The resulting material is an elastomer gel paste of Example 1 with an average particle size of the solvent swollen Example 1 crosslinked elastomer of 45 micrometers.

[0063] Example 2. First, prepare a 10.0 wt% solution of HFP2 in isododecane by adding 10 g of HFP1 and 90 g of isododecane to a first glass jar, seal the jar and roll on a three-mill roll for 48 hours to form a homogenous solution. Then add 20.21 g of the homogenous solution from the first glass jar to a second glass jar along with 0.38 g of diallyl propylene glycol crosslinker and 9.41 g of isododecane. Add a stirring cloth. Place the jar in an 80°C hot water bath and begin stirring. Once the contents reach a temperature of 75-80°C, inject 0.06 g of catalyst into the jar and continue mixing until gelation occurs. Place the jar in a 70°C oven for 4 hours to obtain crosslinked elastomer Example 2.

[0064] Prepare an elastomeric gel paste from Example 2 by placing 26.25g of Example 2 in a Waring Blender and shearing for 20 seconds each at settings 1, 3, and 5 without scraping or stopping between settings. Add 6.06g of isododecane and shear for 30 seconds each at settings 1, 2, and 3. Use intermediate settings to ensure good mixing. The resulting material is the elastomeric gel paste of Example 2.

[0065] Sensory evaluation A sensory evaluation is performed on the elastomer gel paste of Example 2 and DOWSIL™ 9045 silicone elastomer blend (DOWSIL is a trademark of The Dow Chemical Company). DOWSIL™ 9045 silicone elastomer blend is used as a benchmark for sensory performance because it is recognized in the industry to have desirable silky, smooth, and powdery sensory attributes.

[0066] The sensory evaluation is performed by four researchers who are familiar with crosslinked elastomer pastes and have experience in performing sensory evaluations on the skin. Each researcher evaluates the elastomer gel paste of Example 2 and DOWSIL™ 9045 silicone elastomer blend in a blind study with one sample designated as "Sample A" and the other as "Sample B". The researchers are asked to evaluate seven attributes and score each sample on a scale of 1 to 5 for each attribute. Table 5 shows the seven attributes, materials equivalent to values ​​of 1 and 5 for each attribute (values ​​between 1 and 5 have sensory properties between the sensory properties of the equivalent materials), ideal values ​​for the sensory properties, and the average sensory value for each sample assigned by the four researchers.

[0067] [Table 5]

[0068] The paste of Example 2 performs similarly, and in some cases better, in sensory attributes than DOWSIL™ 9045 silicone elastomer blend.

[0069] Organic solvent compatibility The solvent compatibility of Example 1 elastomer gel paste (Example 1 paste) with DOWSIL™ 9045 silicone elastomer blend and DOWSIL™ EL-8040 ID silicone organic blend is evaluated in seven different organic solvents by mixing 8-10 gram batches of 25% by weight Example 1 paste or DOWSIL™ 9045 silicone elastomer blend or DOWSIL™ EL-8040 ID silicone organic blend in the solvent, mixing for 1 minute in a speed mixer, and then transferring to a clear vial. The samples are cured at 25° C. for 12 hours, and then evaluated for clarity and relative thickening according to the following rating rankings. Table 6 lists the seven solvents and the results for Example 1 and DOWSIL™ 9045 silicone elastomer blend.

[0070] Transparency ranking A Transparent B Slightly cloudy C. Cloudy D. Cloudy E Opaque F Incompatible - Heterogeneous mixture

[0071] Viscosity Ranking Assess the viscosity by inverting the vial and observing how the mixture flows: 1 Liquid (equivalent to DOWSIL™ 245 fluid) 3 Injectable (equivalent to 10,000 mm2 / sec (centistokes) polydimethylsiloxane) 5 Injectable (equivalent to 60,000 square millimeters per second (centistokes) of polydimethylsiloxane) 9 Barely injectable (equivalent to 300,000 square millimeters per second (centistokes) of polydimethylsiloxane) 10 It doesn't flow even when inverted.

[0072] [Table 6] Crodamol is a trademark of Croda, INC. * NM = not determined due to inhomogeneous mixture.

[0073] The inventive material has broader solvent compatibility than either DOWSIL™ 9045 Silicone Elastomer Blend or DOWSIL™ 8040 Silicone Organic Elastomer Blend, as evidenced by the homogeneous mixtures obtained with all seven solvents. The inventive material also thickens over more solvents than DOWSIL™ 9045 Silicone Elastomer Blend.

[0074] oil-in-water formulation The paste of Example 1 versus DOWSIL™ 9045 silicone elastomer blend is used to evaluate the ability to form an oil-in-water system.

[0075] An initial mixture is formed by combining the following ingredients, then mixing at 500 revolutions per minute (RPM) with a marine propeller until a uniform mixture is obtained, stopping as necessary to scrape the sides / bottom of the beaker with a spatula: 2 g XIAMETER™ PMX-200 silicone fluid (viscosity of 200 millimeters squared per second (centistokes)), 5 g XIAMETER PMC-0245 cyclopentasiloxane, 3.8 g Dow Corning RM 2051 thickener, and 10 g Example 1 paste or and DOWSIL™ 9045 silicone elastomer blend. XIAMETER is a trademark of Dow Corning Corporation.

[0076] Combine 74 g water and 2 g glycerin in a separate container. Add the resulting mixture in a steady stream to the initial mixture while mixing and increase the mixing speed to 1000 RPM. Add 3 g DOWSIL™ 9509 Silicone Elastomer Suspension (DOWSIL is a trademark of The Dow Chemical Company) while mixing, followed by 0.2 g GLYDANT™ Plus Preservative (GLYDANT is a trademark of Lonza, LLC).

[0077] Both formulations, including Example 1 paste and DOWSIL 9045 silicone elastomer blend, yielded white lotions, demonstrating their ability to easily form oil-in-water systems. Both formulations have similar viscosity and feel on the skin when rubbed in.

[0078] Transparent sunscreen formulation To compare results, clear sunscreen formulations are prepared using the elastomer gel paste of Example 2 (Example 2 Paste) and another using DOWSIL™ 9045 silicone elastomer blend.

[0079] Add 67.45 g of either Example 2 paste or DOWSIL™ 9045 silicone elastomer blend to a speed mixer cup. While mixing at 2300 RPM, add each of the following ingredients in order, simultaneously mixing for 1 minute after each addition to obtain a uniform mixture: 7.5 g octyl methoxycinnamate, 5 g ethylhexyl salicylate, 8 g Crodamol™ GTCC mixed esters, 12 g Cetiol™ OE emollient (Cetiol is a trademark of Cognis IP management GMBH), and 0.05 g DOWSIL™ VM-2270 aerogel particulates (average particle size 5-15 micrometers, surface area 600-800 square meters / gram, and porosity >90).

[0080] Both formulations are colorless. However, only the one with the paste of Example 2 is transparent and stable. The formulation with DOWSIL® 9045 silicone elastomer blend is cloudy and not stable. This demonstrates that the material of the present invention can prepare a transparent sunscreen formulation better than DOWSIL® 9045 silicone elastomer blend.

Claims

1. A composition comprising a crosslinked elastomer comprising a polyolefin backbone crosslinked via a polyether chain, said crosslinked elastomer having a carbon-silicon-carbon bond between said polyolefin backbone and said polyether chain, said crosslinked elastomer being free of Si-O-Si bonds.

2. 2. The composition of claim 1, wherein the polyolefin backbone is an interpolymer of ethylene, octene, and at least one of 7-octenyldimethylsilane and 5-hexenyldimethylsilane, and the polyether chains crosslink by bonding to the silanes.

3. 3. The composition of claim 2, wherein the polyolefin backbone is an interpolymer consisting of polymerized monomer segments of: (a) 20 to 35 mole percent octene; (b) 65 to 80 mole percent ethylene, and (c) 1 to 10 mole percent of any combination of one or more of 7-octenyldimethylsilane and 5-hexenyldimethylsilane.

4. 4. The composition according to any one of claims 1 to 3, wherein the polyether chain comprises polyether units selected from -R-O- groups, where R is an alkylene having from 2 to 8 carbon atoms.

5. The composition of claim 4 , wherein the polyether chain comprises polypropylene oxide.

6. The crosslinked elastomer comprises the following copolymerized polymer segments: (a) 20 to 35 mole percent of a compound having the average chemical structure —CH 2 a combination of one or more of the segments having CHR'-; (b) 65 to 80 mole percent of —CH 2 CH 2 - and (c) 1 to 10 mole percent of —CH 2 CHA-, The mole percentages are based on the moles of copolymerized polymer segments in said crosslinked elastomer, where R′ is an alkyl group having at least 1 and at most 8 carbon atoms, and A has the following average chemical structure (I): -(CH 2 ) n Si(CH 3 ) 2 -B-D (I) [In the formula, n is a value ranging from 4 to 6; B is -(CH 2 ) 3 O (RO) p’ (CH 2 ) 3 where R is an alkylene having at least 2 and at most 8 carbon atoms, and the subscript p' has a value ranging from 15 to 25; D is another A group's -Si(CH 3 ) 2 (CH 2 ) n The composition according to any one of claims 1 to 5, wherein:

7. The composition of any one of claims 1 to 6, wherein the composition further comprises a solvent, and the crosslinked elastomer is solvent swollen such that it becomes a solvent swollen elastomer.

8. The composition of claim 7, wherein the solvent swollen elastomer has an average particle size in the range of 1 to 500 micrometers.

9. 13. A process for producing the composition of claim 1, comprising: (a) a hydrosilane-functional polyolefin that does not contain Si—O—Si bonds; (b) a polyether crosslinker containing at least two terminal alkenyl groups and no Si—O—Si bonds; (c) a hydrosilylation catalyst, and (d) providing a crosslinked elastomer by conducting a hydrosilylation reaction with a reaction composition comprising an organic solvent.

10. The hydrosilane functional polyolefin is (a) 20 to 35 mole percent 1-octene; (b) 65 to 80 mole percent ethylene, and (c) 1 to 10 mole percent of an interpolymer of any combination of one or both of 7-octenyldimethylsilane and 5-hexenyldimethylsilane; 10. The process of claim 9, wherein the mole percentages are based on the total moles of 1-octene, ethylene, 7-octenyldimethylsilane, and 5-hexenyldimethylsilane.